Who’s afraid of the predicate theory of names? - Predelli, Stefano (Springer, 2015)
This essay is devoted to an analysis of the semantic significance of a fashionable view of proper names, the Predicate Theory of names (PT), typically developed in the direction of the Metalinguistic Theory of names (MT). According to MT, ‘syntactic evidence supports the conclusion that a name such as ‘Kennedy’ is analyzable in terms of the predicate (general term) ‘individual named ‘Kennedy’’. This analysis is in turn alleged to support a descriptivist treatment of proper names in designative position, presumably in contrast with theories of names as ‘directly referring rigid designators’. The main aim of this essay is that of questioning the significance of PT and MT as theories of designation: even granting for the argument’s sake that names are analyzable as (metalinguistic) predicates, their designative occurrences may be interpreted in consonance with the dictates of Direct Reference—indeed, in consonance with the radically anti-descriptivist version of Direct Reference I call Millianism.